AKTIVITAS TAREK PUKAT SEBAGAI EKSPRESI SIMBOLIK DALAM KRIYA SENI KAYU - Fitria, Fitria; Asril, Asril; Anshori, Ubai Dillah Al (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Tarek pukat is the activity of fishing communities in catching fish using pukat (nets) by being ditarek (pulled). Tarek pukat activity in modern times is experiencing extinction, the cause is tiger trawling. The tiger trawl has triggered a shift in the value of the Tarek pukat activity. Tarek pukat activity for the people of Aceh has become part of them and their lives. This activity is present because of the results of the thinking of previous people by doing it together and giving birth to interactions between fellow fishing communities. The phenomenon of Tarek pukat activity is explored using a symbolic expression approach. Symbolic expression is a way to express the phenomenon of Tarek pukat activities in works of art by expressing through pouring symbols as a form of value to be presented. The purpose of this creation is to convey messages and provide self-awareness for the general public and the people of Aceh itself. The methods in the creation of this artwork are: exploration, design in the form of experiments, materials, tools, techniques, and realization. The medium used is surian wood, meranti wood, and jackfruit wood. Techniques are scroll and intarsia. The final stage of the creation of finishing works using melamine system, the achievement of the shape and final result of a work can be influenced by the finishing results.The work created by the artist is a two-dimensional work of art in the form of decorative artwork placed on the wall with the title of the work: